(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2024)
The production of high-quality pods bean seeds in the organic production system is a challenge for farmers because there is little information on the appropriate doses of organic compounds to be recommended in the literature. This study aimed to evaluate the yield and physiologic potential of pods beans according to the application of doses of organic compost (earthworm humus). The experimental design used was completely randomized, and the treatments were different doses of organic compost (0, 30, 60, 90, and 120 t ha-1), with four replications. Different yield components were evaluated, and the seed quality was analyzed by the main vigor and germination tests. Organic compost doses influenced most of the seed yield components; however, the physiologic potential and organic fertilization influenced only 1000-seed weight and seedlings dry matter. It is concluded that the doses of organic compost promote the increase in pods bean yield but do not influence the physiologic potential of seeds.